Pengaruh Butterfly Hug Terhadap Tingkat Kecemasan Lansia Di Panti Werdha - Beti Haerani; Nurlaela Isnaini; Lilis Komariah; Imas Yoyoh; Muhammad Amrullah (Poltekkes Kemenkes Maluku, 2025)
Elderly residents in nursing homes are vulnerable to experiencing anxiety that reduces their quality of life. Butterfly Hug was chosen as a non-pharmacological intervention to reduce that anxiety. This study aims to test the effectiveness of Butterfly Hug on the elderly at Panti Werdha Marfati. The research method uses a quantitative approach with a quasi-experimental one group pretest-posttest design. A sample of 30 elderly individuals at Panti Werdha Marfati was selected through purposive sampling according to inclusion and exclusion criteria. The measurement of anxiety levels was conducted using the Geriatric Anxiety Scale (GAS) questionnaire before and after the Butterfly Hug intervention. The intervention was given for 30 minutes, followed by a re-measurement after 3 days. Data were analyzed using the Paired Sample T Test to determine the effect of the Butterfly Hug on elderly anxiety. Research Results: The results of the Paired Sample T Test showed a significant decrease in anxiety scores from an average of 42.60 to 25.03 with a p-value of 0.001 (p < 0.05). The Butterfly Hug intervention proved effective in reducing anxiety levels among the elderly at Panti Werdha Marfati, as evidenced by a significant decrease in anxiety scores after the therapy was administered. It is recommended that the Butterfly Hug be used as a routine non-pharmacological method in the elderly care program at the nursing home to enhance psychological well-being. Further research with a control group design to make it stronger and with a larger sample size.